Improved properties by hydrogen bonding interaction of poly(lactic acid)/palygorskite nanocomposites for agricultural products packaging. Issue 3 (7th October 2013) - Jiang, Yumei; Han, Shunyu; Zhang, Shenggui; Li, Jixin; Huang, Gaobao; Bi, Yang; Chai, Qiang
<x xml:space="preserve">Abstract</x> Poly(lactic acid) (PLA)/palygorskite (PA) nanocomposites were fabricated through melt blending. The significant finding by Fourier transformed infrared spectra and X‐ray photoelectron spectroscopy was that the hydrogen bonding interaction between PA surface and PLA matrix. Due to the hydrogen bonding interaction, the PA particles could be well dispersed and distributed in the PLA matrix, which had been further confirmed by scanning electron microscopy and transmission electron microscopy results. Therefore, PLA/PA nanocomposites revealed the significant improvements in tensile properties, resulting in the potential application for agricultural products packaging. Due to PA aggregates, the degree of hydrogen bonding decreased with the increasing content of PA in the matrix, and the appropriate PA content is 3% (by weight). POLYM. COMPOS., 35:468–476, 2014. © 2013 Society of Plastics Engineers